Increased Expression of lncRNA UCA1 and HULC Is Required for Pro-inflammatory Response During LPS Induced Sepsis in Endothelial Cells - Chen, Ying; Fu, Yao; Song, Yan-fei; Li, Nan (Frontiers in Physiology, 2019)
Systemic uncontrolled inflammatory response, also termed as sepsis, is responsible for many mortalities. Bacterial endotoxin, lipopolysaccharide (LPS), is a major cause of sepsis in endothelial cells. Even though a lot of research has been done to define underlying mechanisms of LPS induced sepsis, the role of long noncoding RNAs (lncRNAs), a group of >200 kb RNAs in sepsis is not well-defined. Expression of pro-inflammatory mediators IL6, ICAM1, and VCAM1 (which encodes interleukin-6, intercellular adhesion molecule-1, and vascular cell adhesion molecule-1, respectively) were determined following LPS treatment of human dermal microvascular endothelial cells (HMECs) for 24 hours to confirm sepsis induction. RNA immunoprecipitation (RIP) analysis was performed using the chromatin modifying proteins (CMPs), heterogeneous nuclear ribonucleoprotein (hnRNP) K and corepressors of the RE-1 silencing transcription factor (coREST) as individual baits. Quantitative real time polymerase chain reaction (qRT-PCR) was performed on RNA isolated from immunoprecipitated pellets for six different lncRNAs. The effect of the differentially expressed lncRNAs were determined by ectopic overexpression of the lncRNAs before induction of sepsis. Expression of IL6, ICAM1, and VCAM1 were significantly upregulated following treatment of the HMECs with LPS for 24 hours confirming induction of sepsis. RIP and qRT-PCR analysis revealed that the lncRNAs HULC, UCA1, and MALAT-1 were significantly enriched with the CMPs after sepsis. RNA interference using siRNAs targeting HULC and UCA1, but not MALAT-1, decreased the expression of IL6, ICAM1, and VCAM1 to endogenous levels. Our results were further validated in an in vivo model of sub-lethal LPS-induced sepsis, whereby siRNA mediated knockdown of UCA1 and HULC lncRNAs prevented induction of VCAM1, ICAM1, and IL6, as assayed by immunohistochemistry. Cumulatively, these results suggest that LPS induced in vitro sepsis in endothelial cells and induction of pre-inflammatory mediators are at least in part due to increased expression of the UCA1 and HULC lncRNAs.